Compound feed as a factor influencing the food quality and safety - Babinszky, László (Acta Agraria Kaposváriensis, 2006)
The paper discusses on the basis of data from the literature and the results of the author's own research work how animal nutrition can be used in the "from farm to fork" chain to influence the quality of pork and poultry meat and the safety of animal products. The relevant results show, that for example in pig nutrition different ileal digestible lysine/energy (IDLYS/DE) ratios will essentially determine the fat content of meat and consequently the quality of the product. The article also highlights the fact, that the dietary IDLYS/DE ratio of genetically improved pigs substantially differs from that of the normal hybrids. While in the diet of a genetically improved pig the required IDLYS/MJ DE ratio is 0.7 g during the first phase of fattening (20–55 kg) and 0.6 g in the second phase of fattening (55–100 kg), these ratios for the normal hybrid are 0.6 and 0.5 g IDLYS/MJ DE, respectively for the two weight categories. This paper also warns, that if animal feed proteins, animal fats and various feed additives are used in a unprofessional manner, they may present a potential risk factor for the safety of the animal food product. The results of the studies discussed lead to the conclusion, that in the "from farm to fork" chain it is extremely important for the safety of products to define clear and unequivocal quality criteria and to establish an official and comprehensive control for each element of the product chain. The author proposes to conduct further systematic studies in accordance with the "from farm to fork" concept in the interest of producing high quality and safe animal food products.
Keywords: animal nutrition; feed quality; food quality; food safety